2020
DOI: 10.1016/j.isci.2020.101769
|View full text |Cite
|
Sign up to set email alerts
|

scREAD: A Single-Cell RNA-Seq Database for Alzheimer's Disease

Abstract: Summary Alzheimer's disease (AD) is a progressive neurodegenerative disorder of the brain and the most common form of dementia among the elderly. The single-cell RNA-sequencing (scRNA-Seq) and single-nucleus RNA-sequencing (snRNA-Seq) techniques are extremely useful for dissecting the function/dysfunction of highly heterogeneous cells in the brain at the single-cell level, and the corresponding data analyses can significantly improve our understanding of why particular cells are vulnerable in AD. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 33 publications
0
80
0
Order By: Relevance
“…(D) TREM2 upregulations in AD postmortem samples (p < 0.05). The snRNAseq gene expression data were acquired from scREAD [45]. (E) Trem2 upregulations in microglia of 5XFAD and APP/PS1 AD mouse models (p < 0.05).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(D) TREM2 upregulations in AD postmortem samples (p < 0.05). The snRNAseq gene expression data were acquired from scREAD [45]. (E) Trem2 upregulations in microglia of 5XFAD and APP/PS1 AD mouse models (p < 0.05).…”
Section: Introductionmentioning
confidence: 99%
“…(E) Trem2 upregulations in microglia of 5XFAD and APP/PS1 AD mouse models (p < 0.05). The snRNAseq gene expression data were acquired from scREAD [45].…”
Section: Introductionmentioning
confidence: 99%
“…For single-cell expression studies, the scREAD database (Available from: https://bmbls.bmi.osumc.edu/scread/) was interrogated, to further characterize IFITM3' and FYN's expression in AD-donated tissue 6 (See Supplementary Materials 1 -Expanded Methods for further details).…”
Section: Single Cell Rna Transcriptomicsmentioning
confidence: 99%
“…Dataset used in this study were anonymized; The specific protocol for informed consent and institutional review board approval can be found in detail elsewhere 5,6 .…”
Section: Ethical Approvalmentioning
confidence: 99%
See 1 more Smart Citation